CP-182 Pharmaceutical validation of treatments: From the pharmacy or at the hospital wards?. (14th February 2016) - De Castro Julve, M; García-Pelaez, M; Trias, L Borràs; Comas, G Puig; Torner, MQ Gorgas
Abstract : Background: Hospital pharmacists validate many treatments per day, mostly not knowing the hospitalised patient's current situation and with little interaction with the medical team and nurses who care for these patients. Purpose: To describe differences in pharmacist interventions when validation of treatments is performed in the hospital ward and when it is performed in the pharmacy department. Material and methods: Prospective-retrospective descriptive observational study. Pharmacist interventions in a particular medical ward were recorded over 1 month when transcription and validation of admitted patients' medications took place in the hospitalisation area (on-site validation). They were compared with pharmacist interventions recorded during the previous month in the same ward, where transcription and validation took place in the pharmacy (centralised validation). Results: During the on-site validation period, 41% of 174 patients who were admitted to that ward received at least one pharmaceutical intervention, with a total of 142 interventions. The most frequent interventions in this period were: prescription error (42; 29%), intervention related to dispensation (29; 20%), dose or posology recommendation (19; 13%), administration recommendation (15; 10.5%), therapeutic equivalent replacement (8; 6%) and related to duration of treatment (8; 6%). During the centralised validation period, 31% of 203 patients who were admitted received at least one pharmaceutical intervention with a total of 78 interventions. The most frequent interventions in this month were: prescription error (27; 35%), dose or posology recommendation (14; 18%), therapeutic equivalent replacement (13; 17%), duplicity of treatments (5; 6%) and omission of required medication (5; 6%). Conclusion: Validation of prescriptions in the hospital ward allows the pharmacist to make more recommendations and interventions related to the patient's treatment. The main differences in the type of interventions were related to medication administration and dispensing. It is important to promote the presence of pharmacists in healthcare teams in order to provide patients with the best possible healthcare. No conflict of interest.